The perspective of indigenous culture - A case study of the Truku tribe in East Taiwan - PI-CHI CHOU; SU-FANG WU; SHAO-CHI HSU; YA-CHING CHOU (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aims to find out if and how the Truku people of East Taiwan have managed to keep their traditions alive over time. Methodology Archival research, participant observation, and the use of a SWOT analysis all contribute to the qualitative nature of this investigation.Findings: The Truku people, it can be said with confidence, serve as a prime illustration of the maturation of both tribal culture and the Seejoq language. The benefits and drawbacks, opportunities, and threats of tourism development for the Truku tribe have all been critically analyzed in this study. It has been discovered that the rituals of the May Bari of Truku can significantly revive the Truku people. Created based on its beliefs and practices.Implications/Novelty: Our original contribution is that we looked at how tribal pride in their ancestry has changed over time. This research bolsters the case for the widespread acceptance of tribal people into modern society’s networks, where they enjoy the same rights and freedoms as everyone else, not just in isolated communities.